The Meaning of Religious Moderation According to Franz Magnis-Suseno: A Phenomenological Approach - R.F. Bhanu Viktorahadi (Jurnal Iman dan Spiritualitas, 2022)
Religious moderation is necessary to guarantee social stability against the unwanted ideological force and even physical collisions in society. Social and religious lives are not isolated but must be integrated into one another. Building an educated and open-minded religious community is required to achieve this goal. The ideal religious moderation should be created through active participation from all members of diverse religious communities to achieve the same goals based on togetherness, inclusive attitude, respect, and mutual understanding related to performing certain rituals and doctrines of each religion. The variety of typologies of interfaith relations, such as exclusivism, inclusivism, and pluralism, are commonly formulated to bring these diversities into the further step of harmonious religious dialogues. This article uses the phenomenological approach in studying the meaning of religious moderation, according to Franz Magnis-Suseno. Specifically, according to Magnis-Suseno, someone just can talk about religious moderation if there is a willingness to accept and recognize plurality. That is, assuming the difference. Religious moderation means getting relatives or groups, even though their views, beliefs, and beliefs are different.